1974
DOI: 10.1002/jlac.197419740803
|View full text |Cite
|
Sign up to set email alerts
|

Cycloadditionen mit Azabenzolen, VII1) Reaktion von Pyrimidinen mit N,N‐Diäthyl‐1‐propinylamin

Abstract: Die Pyrimidincarbonsaureester 2a-2e reagieren rnit N,N-Diathyl-I-propinylamin (1) in einer Diels-Alder-Reaktion rnit inversem Elektronenbedarf zu den Pyridinderivaten 3a-3f. Es werden Regeln fur die Orientierung der beiden Reaktionspartner zueinander abgeleitet. Cycloaddition Reactions with Azabenzenes, VIL'). -Reaction of Pyrimidines with N,N-Diethyl- 1-propynylamineThe pyrimidinecarboxylates 2a-2e react with N,N-diethyl-I-propynylamine (1) via a Diels-Alder reaction with inverse electron demand to give the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

1975
1975
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 4 publications
0
17
0
1
Order By: Relevance
“…Pyrimidines are not reactive dienes in general, and their cycloaddition reactions require high temperatures. Nevertheless, Neunhoeffer reported in 1974 that electron‐rich ynamines were competent partners in [4+2]/retro‐[4+2] reactions leading to aminopyridines in moderate yields (Scheme ) . The sequence proceeds through a bicyclic intermediate (e.g., 38 ; Scheme ) that spontaneously expels a nitrile.…”
Section: [4+2] Cycloadditions Of Ynaminesmentioning
confidence: 99%
See 3 more Smart Citations
“…Pyrimidines are not reactive dienes in general, and their cycloaddition reactions require high temperatures. Nevertheless, Neunhoeffer reported in 1974 that electron‐rich ynamines were competent partners in [4+2]/retro‐[4+2] reactions leading to aminopyridines in moderate yields (Scheme ) . The sequence proceeds through a bicyclic intermediate (e.g., 38 ; Scheme ) that spontaneously expels a nitrile.…”
Section: [4+2] Cycloadditions Of Ynaminesmentioning
confidence: 99%
“…Inspired by the elegant transformations of pyrimidines into pyridines through inverse‐electron‐demand Diels–Alder reactions reported by the groups of Neunhoeffer, Miyashita, Ohsawa,, and van der Plas, we hypothesized that ynamides 141 might be competent partners in such pericyclic sequences in either intra‐ or intermolecular fashion (Scheme ). As detailed in Section 2, pyrimidines are quite unreactive azadienes, but this downside should be balanced by their commercial availability, low cost, and unsurpassed structural diversity in relation to triazines or tetrazines.…”
Section: Inverse‐electron‐demand [4+2] Cycloadditions Between Ynammentioning
confidence: 99%
See 2 more Smart Citations
“…Diels-Alder cycloadditions between alkynes and pyrimidines are classified as inverse electron demand [4ps+2ps] cycloadditions that lead to pyridines upon spontaneous retro-Diels-Alder reaction of the primary cycloadduct. [1][2][3][4][5] A limitation of this conceptually interesting synthesis of pyridines are the high temperature (up to 280 °C under classical conditions 6 ) and very long reaction times that are required [7][8][9] to overcome the intrinsic lack of reactivity of these aza-dienes. [10][11][12][13][14][15][16][17][18][19] On the other hand, we recently reported that pyrimidines substituted in the 2-position by an (alkynyl)hydrazone could be exceptionally activated towards intramolecular [4ps+2ps] cycloadditions by a simple activation (Scheme 1, A).…”
Section: Introductionmentioning
confidence: 99%